Sistem Informasi Penjualan Dalam Peningkatan Layanan Digital Berbasis Web - Hasibuan, Tuhfatul Habibah (Lembaga Pengembangan Kinerja Dosen, 2023)
In an era of technological advancement, access to fast, accurate and efficient information has become an important requirement. This research focuses on the application of information systems in helping data management and customer service in various sectors, especially in the food business. The use of a web-based sales information system provides a solution to overcome various problems faced by small companies, such as sales data management that is prone to errors and loss of notes. By applying the Waterfall Method as a sequential and structured system development approach. With this technology, companies can increase effectiveness and productivity in handling management problems and provide better service to customers. The results of system testing show that all system features are valid and run as expected. research suggestions related to system features are additional features to find out the status of orders placed by visitors so that an estimation feature can be carried out from the time of the message to completion.